A multiple case study of teachers referring to their own religious beliefs in mathematics teaching. Issue 3 (1st October 2016) - Chan, Yip-Cheung; Wong, Ngai-Ying
Abstract: There is a need to integrate religious education and spiritual education across school curriculum. This paper reports one of the few empirical studies on bridging the intention-practice gap in classrooms. Six school teachers deliberately designed and implemented mathematics lessons which referred to their own religious beliefs in teaching. It unfolds teachers' intention to enact their religious beliefs in mathematics classroom teaching. Different modes were identified. Implications to religious education in schools are offered.